Motion of the vitreous humour in a deforming eye-fluid-structure interaction between a nonlinear elastic solid and viscoleastic fluid - Tůma, Karel; Stein, Judith; Friedmann, Elfriede (Applied mathematics and computation, 2018)
We study the motion of vitreous humour in a deforming eyeball. From the mechanical and computational perspective this is a task to solve a fluid-structure interaction problem between a complex viscoelastic fluid (vitreous humour) and a nonlinear elastic solid (sclera and lens). We propose a numerical methodology capable of handling the fluid-structure interaction problem, and we demonstrate its applicability via solving the corresponding governing equations in a realistic geometrical setting and for realistic parameter values. It is shown that the choice of the rheological model for the vitreous humour has a negligible influence on the overall flow pattern in the domain of interest, whilst it has a significant impact on the mechanical stress distribution in the domain of interest.
Available online 8 May 2018
Gesehen am 03.09.2018